Cardiomyopathy in Offspring of Pregestational Diabetic Mouse Pregnancy. (26th June 2014) - Dowling, Daniel; Corrigan, Niamh; Horgan, Stephen; Watson, Chris J.; Baugh, John; Downey, Paul; McAuliffe, Fionnuala M.
Abstract : Purpose . To investigate cardiomyopathy in offspring in a mouse model of pregestational type 1 diabetic pregnancy. Methods . Pregestational diabetes was induced with STZ administration in female C57BL6/J mice that were subsequently mated with healthy C57BL6/J males. Offspring were sacrificed at embryonic day 18.5 and 6-week adolescent and 12-week adult stages. The size and number of cardiomyocyte nuclei and also the extent of collagen deposition within the hearts of diabetic and control offspring were assessed following cardiac tissue staining with either haematoxylin and eosin or Picrosirius red and subsequently quantified using automated digital image analysis. Results . Offspring from diabetic mice at embryonic day 18.5 had a significantly higher number of cardiomyocyte nuclei present compared to controls. These nuclei were also significantly smaller than controls. Collagen deposition was shown to be significantly increased in the hearts of diabetic offspring at the same age. No significant differences were found between the groups at 6 and 12 weeks. Conclusions . Our results from offspring of type 1 diabetic mice show increased myocardial collagen deposition in late gestation and have increased myocardial nuclear counts (hyperplasia) as opposed to increased myocardial nuclear size (hypertrophy) in late gestation. These changes normalize postpartum after removal from the maternal intrauterine environment.